The Effect of Metacognition Strategies Toward Mastery of Concepts and Scientific Attitude of Students Class XI in Learning Human Reproductive System - Widianingsih, Anugrah Ayumaharani; Wulan, Ana Ratna (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The purpose of this research was to investigate effect of metacognition strategies toward mastery of concepts and scientific attitude of high school students in learning human reproductive system. Research was conducted in May 2015, with Causal-comparative method and Ex-post facto approach. Population was 11th grade students of SMAN 1 North Tambun, SMAN 2 North Tambun, Secondary Vocational School of Health Zam-zam Kurnia, and Secondary Vocational School of Nursing Satria Nusantara, Subdistrict North Tambun, Bekasi, academic year 2014/2015. The sample consisted of 100 students of 11th grade high school who had been studying human reproductive system in biology major, with cluster random sampling. The data were collected by test method for mastery of concepts, Scientific Attitude Scale, and Metacognition Strategy Questionnaire. Questionnaire of Metacognition Strategy used to classify students into some group (students with Self-awareness Strategies (A), Modifying Strategies (B), and Imitation Strategies (C)). Data were analysed by MANOVA using Software SPSS 20. The analysis showed that: 1) the mean mastery of concepts and scientific attitude of students were different for metacognition strategies types, 2) difference score was significant for mastery of concepts but not found in the scientific attitude of students, 3) metacognition strategies affect the acquisition score of mastery of concepts but does not for scientific attitude of students, 4) Metacognition strategies A and metacognition strategies C was affect of the score ofÂ  the mastery of concepts.Keywords:Metacognition Strategies, Mastery of Concepts, Scientific Attitude, Human Reproductive System